2018
DOI: 10.5588/ijtld.17.0672
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis infection and disease in people living with HIV in countries with low tuberculosis incidence

Abstract: In countries with low tuberculosis (TB) incidence, TB is concentrated in vulnerable populations, including people living with the human immunodeficiency virus (PLHIV), who have a substantially greater risk of TB than people without HIV. We searched PubMed, EMBASE and Web of Science for studies evaluating the risk factors for latent tuberculous infection (LTBI) or active TB in PLHIV in countries with TB incidence 10 per 100 000 population. Due to the number of risk factors evaluated and heterogeneity in study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
5
8
0
Order By: Relevance
“…In our study, there was a drop of TB incidence (in HIV care) by three-folds following HAART initiation. Patients with higher CD4 and/or CD4/CD8 ratio were at lower risk of TB disease development, as observed in our and previous studies 24,27,28 , as a result of immune recovery 18,19 . The results were consistent with those reported in a study showing the four times higher TB incidence among heterosexual HIV patients not on HAART 29 , and conclusion from a systematic review 19 .…”
Section: Discussionsupporting
confidence: 89%
“…In our study, there was a drop of TB incidence (in HIV care) by three-folds following HAART initiation. Patients with higher CD4 and/or CD4/CD8 ratio were at lower risk of TB disease development, as observed in our and previous studies 24,27,28 , as a result of immune recovery 18,19 . The results were consistent with those reported in a study showing the four times higher TB incidence among heterosexual HIV patients not on HAART 29 , and conclusion from a systematic review 19 .…”
Section: Discussionsupporting
confidence: 89%
“…30 This finding also revealed that patients with severe immunosuppression (CD4% <200 cell/mm3) were 2.12 times higher risk of developing TB than those with higher CD4 in adults. This was consistent with various studies (28,29,32,35,36) in which sever immune suppression fastened the progression of latent TB to active disease (2). This is because HIV kills TB protective immune cells among HIV patients.…”
Section: Discussionsupporting
confidence: 92%
“…Studies by [10] and [11] in various outbreak settings confirm that HIV co-infection does intensify the progression of latent TB to active TB disease. The diagnosis of TB in the HIV epidemic remains extremely challenging because of the difficulty in differentiating between reactivation and recent infections [12]. The risk of infection or reinfection is dependent on the source case numbers in various congregate settings including households and health-care facilities [5].…”
Section: Introductionmentioning
confidence: 99%